Parents' perceptions of the implementation of the independent curriculum at State Senior High School 13 Makassar - Pratiwi, Anisya Anindya; Sumilih, Dimas Ario (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2025)
The Merdeka Curriculum, one of the policy programs under the umbrella of the Merdeka Belajar movement, was designed as a learning recovery effort developed by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) within a more flexible framework, focusing on providing essential materials, as well as developing student character and competency. Through this framework, students are expected to receive more meaningful and in-depth learning. This study aims to elaborate on the opinions of parents of students at SMA Negeri 13. This research is qualitative, where data is collected through observation, interviews, and documentation. The results show that parents highly appreciate the Merdeka Curriculum because it stimulates students' creativity, innovation, and thinking skills that are in line with the noble values ​​of the nation's culture stated in Pancasila